Socio-economic changes and sacred groves in South India: Protecting a community-based resource management institution - M.G. Chandrakanth, Mahadev G. Bhat and M.S. Accavva (Natural Resources Forum 28 (2004) 102-111, 2004)
The sacred groves along the forest belts of south India, which were traditionally managed by village communities, are gradually disappearing. This study conducts an analysis of how this community-based resource management institution has evolved over time and what socio-economic factors have caused its gradual disintegration. commercial agriculture, changing demographics and weak property-rights systems are found to be some of the enabling factors. While the grass-roots enthusiasm to save the sacred groves is still alive, government action is needed to strengthen the traditional village organizations, which are still perhaps in the best position to manage local resources. Several economic and financial incentive mechanisms at the local level that might lead to more efficient and equitable resource use outcomes are suggested.